Effects Hydrocortisone on the Body Weight of the Pregnant Rabbits and their Embryo with Histological Effects Skin, Stomach and Small Intestine of Embryos - Abid AL.Shammary1, Rasha Noori Abid AL-Shammary1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The aim of the study was to investigate the effects hydrocortisone of on the body weight of the pregnant rabbits and their embryo with histological effects pregnant skin ,stomach and intestine of embryos for 45 days. The rabbit were randomly divided into two equal groups (control and one treated groups), and the animals were treated as follow: 1- Control group C. (n = 12) received Distilled water 1ml /kg b.w five times a week intramuscular for 26days. 2-Treatment group. (n=12) treated daily with hydrocortisone 100mg/kg b.w/day/ intramuscular for 26 days. The body weight of the animals detected at the 1th,7h ,14th ,21th and 26thdays of the experimental period. At 26 days animals sacrificed and embryos weighted and skin ,stomach , intestine were removed and taken for histopathological study. The present study showed that treatment with hydrocortisone causes a significant decrease in body weight of embryos and pregnant rabbits .As a conclusion: hydrocortisone cues decrease body weight of embryos and pregnant rabbits.